The Leptinotarsa forkhead transcription factor O exerts a key function during larval-pupal-adult transition. (July 2021) - Kang, Wei-Nan; Wang, Bing-Yao; Fu, Kai-Yun; Guo, Wen-Chao; Jin, Lin; Li, Guo-Qing
Graphical abstract: Highlights: 20E stimulates the expression of LdFoxO . Silencing LdFoxO represses 20E signaling and reduces larval weight. RNAi of LdFoxO impairs larva-pupa-adult transition. 20E or JH consumption cannot restore defects in LdFoxO depleted animals. Abstract: Forkhead box O (FoxO) protein, a major downstream transcription factor of insulin/insulin-like growth factor signaling/target of rapamycin pathway (IIS/TOR), is involved in the regulation of larval growth and the determination of organ size. FoxO also interacts with 20-hydroxyecdysone (20E) and juvenile hormone (JH) signal transduction pathways, and hence is critical for larval development in holometabolans. However, whether FoxO plays a critical role during larval metamorphosis needs to be further determined in Leptinotarsa decemlineata . We found that 20E stimulated the expression of LdFoxO . RNA interference (RNAi)-aided knockdown of LdFoxO at the third-instar stage repressed 20E signaling and reduced larval weight. Although the resultant larvae survived through the third-fourth instar ecdysis, around 70% of the LdFoxO depleted moribund beetles developmentally arrested at prepupae stage. These LdFoxO depleted beetles were completely wrapped in the larval exuviae, gradually darkened and finally died. Moreover, approximately 12% of the LdFoxO RNAi beetles died as pharate adults. Ingestion of either 20E or JH by the LdFoxO depletion beetles excessively rescued the corresponding hormonal signals, but could not alleviate larval performance and restore defective phenotypes. Therefore, FoxO plays an important role in regulation of larval-pupal-adult transformation in L. decemlineata, in addition to mediation of IIS/TOR pathway and stimulation of ecdysteroidogenesis.